Ritual, ideation and performance: a case study of multimedia in anthropological research - the Mambila Nggwun ritual (paper presented to 16th European Meeting on Cybernetics and Systems Research (EMCSR), April 2-5, 2002) - Zeitlyn, D; Fischer, M (Austrian Society for Cybernetic Studies, 2002)
The Mambila Nggwun ritual is partly a war dance in which the domination of the outlying hamlets by the village centre is dramatically enacted. Principally, it is a celebration of the institution of chief, and it includes many rites to strengthen the chief. Prior to 1997 Zeitlyn had documented the ritual on many occasions, based on his participation and discussions with a range of Mambila consultants. In 1997 Zeitlyn and Fischer returned to Somi to further investigate the ritual by working with local consultants to author visual documents based on the ritual. What we found was puzzling. Although everyone could produce a schematic specimen verbal account of Nggwun with a simple chronological description of its structure, no one we worked with could produce either a description or reliable judgements about order or structure based on audio-visual materials depicting an occurrence of the ritual six months earlier, despite being able to recognize each individual depiction.